A Review on Waterborne Thermosetting Polyurethane Coatings Based on Castor Oil: Synthesis, Characterization, and Application. Issue 6 (13th April 2018) - Panda, Siva Sankar; Panda, Bishnu P.; Nayak, Sanjay K.; Mohanty, Smita
ABSTRACT: Waterborne polyurethane coatings made from castor oil as polyol resource, replacing oil from fossil fuels are attracting lot of recognition during recent decades. In this review, castor oil and its modifications to synthesize various biobased waterborne polyurethane and their nanocomposite systems have been addressed. Various synthesis procedures for waterborne polyurethane dispersions and their applications as a coating material have been described. This review will be helpful to the green research community for selection of monomer and further development of biobased waterborne polyurethane utilizing advanced technology. GRAPHICAL ABSTRACT: